The Impact of Knowledge Sharing on Employees Satisfaction: Review - Hammouri, Qais; Altaher, Asmahan (International Journal of Psychosocial Rehabilitation, 2020)
Knowledge sharing (KS) is one of the most important strategies that help organizations to extract and codify tacit knowledge. This paper aimed to develop a theoretical framework helps to test the relationship between knowledge sharing techniques and employees satisfaction through reviewed the literature in such domain. The Eight factors were extracted from the literature that are related to the knowledge sharing techniques: formal training, written reports, periodic meetings and workshops, mentoring and coaching programs, face to face interaction, knowledge sharing systems, email and cloud computing. The researchers recommend that the companies need to improve their supports for the use of knowledge sharing to enhance the employees satisfaction. A proposed model is depicted at the end for future testing.